2019
DOI: 10.4049/jimmunol.1900262
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide-Stimulated Human Fetal Membranes Induce Neutrophil Activation and Release of Vital Neutrophil Extracellular Traps

Abstract: Preterm birth is a major contributor to neonatal mortality and morbidity, and infection is a major risk factor. Chorioamnionitis, inflammation of the placenta, and fetal membranes (FMs) are commonly observed in preterm birth and are characterized by neutrophil infiltration. However, interactions between FMs and neutrophils remain incompletely understood. The objectives of this study were to determine how FMs, with or without bacterial LPS stimulation, affect neutrophil recruitment, activation, and the formatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 59 publications
3
43
0
Order By: Relevance
“…Indeed, there were no changes in the frequency of T cell, NK cells, iNKT cells in the chorio-decidua after LPS in our model. Recently, Tong et al reported that induction of neutrophil activation and Neutrophil Extracellular Trap (NET) release is mediated at least in part by fetal membrane-derived TNFα (11). We observed that the inhibition of TNF-signaling decreased LPS-induced neutrophil counts by 80% in the choriodecidua and by 50% in the amniotic fluid.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…Indeed, there were no changes in the frequency of T cell, NK cells, iNKT cells in the chorio-decidua after LPS in our model. Recently, Tong et al reported that induction of neutrophil activation and Neutrophil Extracellular Trap (NET) release is mediated at least in part by fetal membrane-derived TNFα (11). We observed that the inhibition of TNF-signaling decreased LPS-induced neutrophil counts by 80% in the choriodecidua and by 50% in the amniotic fluid.…”
Section: Discussionmentioning
confidence: 52%
“…Here, we show that amnion expression of neutrophil chemokines is also TNFdependent. IL1 inhibition has overlapping results compared to TNF inhibition in the same rhesus macaque model of LPS-induced IUI (10,11). However, a notable difference is inhibition of LPS-induced AF PGE 2 levels with IL1-blockade FIGURE 9 | Model for pathogenesis of intrauterine infection/inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Human neutrophils were isolated as previously described (48). Briefly, peripheral blood was collected from healthy, nonpregnant women and used immediately.…”
Section: Human Neutrophil Preparationmentioning
confidence: 99%
“…2. PBMC were added to the upper chamber and then exposed to CM in the lower chamber obtained from: (1) DSCs treated with vehicle (control) or (2) DSCs treated with LPS (100 ng/mL) for 48 h. This concentration of LPS has no detrimental effect on DSCs [60][61][62][63] . As shown in Fig.…”
Section: Bacterial Lipopolysaccharide (Lps) Inhibits H3k27me3 Modificmentioning
confidence: 99%